How Can the Typhoid Fever Surveillance in Africa and the Severe Typhoid Fever in Africa Programs Contribute to the Introduction of Typhoid Conjugate Vaccines?. (30th October 2019) - Jeon, Hyon Jin; Im, Justin; Haselbeck, Andrea; Holm, Marianne; Rakotozandrindrainy, Raphaël; Bassiahi, Abdramane Soura; Panzner, Ursula; Mogeni, Ondari D; Seo, Hye Jin; Lunguya, Octavie; Jacobs, Jan; Okeke, Iruka N; et al.
Abstract: Background: The World Health Organization now recommends the use of typhoid conjugate vaccines (TCVs) in typhoid-endemic countries, and Gavi, the Vaccine Alliance, added TCVs into the portfolio of subsidized vaccines. Data from the Severe Typhoid Fever in Africa (SETA) program were used to contribute to TCV introduction decision-making processes, exemplified for Ghana and Madagascar. Methods: Data collected from both countries were evaluated, and barriers to and benefits of introduction scenarios are discussed. No standardized methodological framework was applied. Results: The Ghanaian healthcare system differs from its Malagasy counterpart: Ghana features a functioning insurance system, antimicrobials are available nationwide, and several sites in Ghana deploy blood culture–based typhoid diagnosis. A higher incidence of antimicrobial-resistant Salmonella Typhi is reported in Ghana, which has not been identified as an issue in Madagascar. The Malagasy people have a low expectation of provided healthcare and experience frequent unavailability of medicines, resulting in limited healthcare-seeking behavior and extended consequences of untreated disease. Conclusions: For Ghana, high typhoid fever incidence coupled with spatiotemporal heterogeneity was observed. A phased TCV introduction through an initial mass campaign in high-risk areas followed by inclusion into routine national immunizations prior to expansion to other areas of the country can be considered. For Madagascar, a national mass campaign followed by routine introduction would be the introduction scenario of choice as it would protect the population, reduce transmission, and prevent an often-deadly disease in a setting characterized by lack of access to healthcare infrastructure. New, easy-to-use diagnostic tools, potentially including environmental surveillance, should be explored and improved to facilitate identification of high-risk areas.